UGRA 82 is it digital or film? - (:unkn) unknown (My University, 2006)
The technological development in the printing industry has resulted in high expectations by customers in the printing quality. In relation to these customer demands, investigators looked for different solutions for better image quality. UGRA 82 is an internationally accepted standard control strip which controls both the pose quality of the plate and secondly the printed image quality. In the presents study, the UGRA 82 control strip, which was manufacturally prepared to become sensitive to the light, was passed through the surface of the conventional plate by imposing in two ways. UGRA 82 control strip prepared as an original film by UGRA and the digital UGRA 82 film in the EPS folder format prepared in the computer by UGRA were imposed into film and montaged with original UGRA 82. This montage was imposed into the plate in the optimum conditions. The dot gain values were obtained by measuring the dot values with a densitometer from UGRA 82 at the surface of the plate. A print was prepared on a coated paper with a computer controlled ofset print machine. The dot gain was measured by a spectrophotometer via UGRA 82 printed to the paper. Finally, the qualities of digital and film UGRA 82 were compared.